If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying s + 14 = 57 Reorder the terms: 14 + s = 57 Solving 14 + s = 57 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + s = 57 + -14 Combine like terms: 14 + -14 = 0 0 + s = 57 + -14 s = 57 + -14 Combine like terms: 57 + -14 = 43 s = 43 Simplifying s = 43
| x+11=-3 | | .5x+3=7 | | x-11=-3 | | -c+2=51 | | 73=6x+46 | | 6c^2-28c+16= | | 2n-6n=12-2n | | 6y+3x=-12 | | 3y+(5+6y)=3y-5 | | 4b^2-15b+9= | | 2n-9=4n+3 | | 3p^2-7p-66=0 | | 4m-8=40 | | 3x+6y=-12 | | 20s^2+17s-63= | | 3x^3+18=x(2x+27) | | d=6 | | 20v^2+13v-15= | | 2k^2-9k+7=0 | | q=3h+3x | | 2x=12-10 | | -8x-3y=2 | | 12c^2+13c-35= | | x=-40 | | 0+0.1x=6+-10 | | 3x+8x=77 | | 6t-2t=4 | | 8n-2=26+4n | | 7m-4=-4+m | | (2n-5)(7n+7)=0 | | 4v^2+9v+5= | | -15=9y-6/8-5y+1/2 |